2013
DOI: 10.1371/journal.pbio.1001541
|View full text |Cite
|
Sign up to set email alerts
|

PICK1 and ICA69 Control Insulin Granule Trafficking and Their Deficiencies Lead to Impaired Glucose Tolerance

Abstract: PICK1 and ICA69, proteins containing a BAR domain, regulate the biogenesis and maturation of insulin granules in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
109
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(129 citation statements)
references
References 31 publications
18
109
2
Order By: Relevance
“…5H-J). Moreover, consistent with previous observations in Drosophila brain (Cao et al, 2013), we found significant reduction in ICA69 levels at Drosophila NMJs in mef2-Gal4-driven PICK1 RNAi animals (control, 100.0±3.9; PICK1 RNAi, 72.1±5.3) (Fig. 5K-M).…”
Section: Synaptic Levels Of Iglur Subunits Are Tightly Regulated By Tsupporting
confidence: 92%
See 2 more Smart Citations
“…5H-J). Moreover, consistent with previous observations in Drosophila brain (Cao et al, 2013), we found significant reduction in ICA69 levels at Drosophila NMJs in mef2-Gal4-driven PICK1 RNAi animals (control, 100.0±3.9; PICK1 RNAi, 72.1±5.3) (Fig. 5K-M).…”
Section: Synaptic Levels Of Iglur Subunits Are Tightly Regulated By Tsupporting
confidence: 92%
“…recent study has shown that ICA69 and PICK1 stability is interdependent in Drosophila brain (Cao et al, 2013). Thus, it is likely that iGluR clusters at the NMJ are regulated by levels of ICA69 and PICK1 in muscles.…”
Section: Regulation Of Glutamate Receptor Clusters By Ica69mentioning
confidence: 97%
See 1 more Smart Citation
“…ICA69 also contains an N-terminal BAR domain. ICA69 forms heteromeric BAR domain dimers with PICK1 and is the major binding partner for PICK1 in the brain and pancreas (Cao et al, 2007(Cao et al, , 2013. ICA69 inhibits synaptic targeting of AMPA receptors by restricting the localization of PICK1 to dendritic shafts (Cao et al, 2007;Xu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the BAR domain complex of PICK1 and ICA69 is associated with insulin granule trafficking in pancreatic β-cells. Deficiency of PICK1 leads to abnormal trafficking of insulin granules and glucose intolerance (Cao et al, 2013;Holst et al, 2013). Moreover, this complex has also been found to promote the budding of growth hormone granules from the Golgi apparatus in the pituitary gland (Holst et al, 2013).…”
Section: Introductionmentioning
confidence: 99%